2019
DOI: 10.18632/oncotarget.27155
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cathepsin D is required for L1-mediated colon cancer progression

Abstract: Hyperactivation of Wnt/β-catenin target genes is considered a key step in human colorectal cancer (CRC) development. We previously identified the immunoglobulin-like cell adhesion receptor L1 as a target gene of β-catenin/TCF transactivation that is localized at the invasive edge of CRC tissue. Using gene arrays, we discovered a number of downstream target genes and signaling pathways conferred by L1 overexpression during colon cancer progression. Here, we have used a proteomic approach to identify proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 40 publications
0
33
0
2
Order By: Relevance
“…We wished to determine the proteins and signaling pathways that are involved in L1-mediated progression of colorectal cancer (CRC). We employed the LS 174T human CRC cell line stably overexpressing L1 and compared the proteins secreted into the conditioned medium of these cells using mass spectrometry [12], to those of cells transfected with the control pcDNA3 plasmid. Among the proteins in the culture medium whose levels were most dramatically induced in L1-overexpressing CRC cells, we identified the ubiquitin-like interferon-stimulated protein of 15 kDa (ISG15, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We wished to determine the proteins and signaling pathways that are involved in L1-mediated progression of colorectal cancer (CRC). We employed the LS 174T human CRC cell line stably overexpressing L1 and compared the proteins secreted into the conditioned medium of these cells using mass spectrometry [12], to those of cells transfected with the control pcDNA3 plasmid. Among the proteins in the culture medium whose levels were most dramatically induced in L1-overexpressing CRC cells, we identified the ubiquitin-like interferon-stimulated protein of 15 kDa (ISG15, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of L1 in CRC cells confers increased proliferation in low serum, enhanced motility, tumorigenesis and liver metastasis [5]. Using gene microarray and proteomic analyses, we identified a number of genes and signaling pathways induced by L1 overexpression in CRC cells and validated their relevance to CRC development [612]. In this study, using a proteomic analysis of proteins whose level is increased in the secretome of L1-overexpressing CRC cells, we found that the ubiquitin-like interferon-induced gene 15 (ISG15) [13], is one of the proteins whose expression is dramatically increased in L1-overexpressing CRC cells.…”
Section: Introductionmentioning
confidence: 99%
“…The conditioned media (CM) from the different available CRC cell lines is the most analyzed secretome sample. In addition to being xenograft tumor models for CRC, human colon adenocarcinoma cell lines, such as CaCo-2, LIM1215, HCT-116 and HT-29, are used as in vitro CRC model systems to analyze intracellular and secreted proteins from intestinal epithelial cells [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Secretome Samplesmentioning
confidence: 99%
“…Given the positive correlation between immunoglobulin-like cell adhesion receptor L1 (L1CAM) expression and CRC tumorigenesis [ 97 ], Basu and colleagues recently found, in L1CAM-overexpressing CRC cells, more than 10-fold increased levels of nine secreted proteins [ 41 ]. Among these, they confirmed that increased levels of cathepsin D (CTSD) enhance the motility, tumorigenesis and liver metastasis of CRC cells by activation of Wnt/β-catenin signaling.…”
Section: Biomarker Discovery For Crc Early Diagnosis By Secretomementioning
confidence: 99%
See 1 more Smart Citation